Remission and Recovery in Schizophrenia: Practitioner and Patient Perspectives - Davidson, Larry (Oxford University Press, 2008)
Schizophrenia remains a complex, dynamic, multi-dimensional, and poorly understood condition. Although the concept of heterogeneity in outcome has conceptually overturned the post Kraepelinian legacy of progressive deterioration, a number of factors appear to contribute to perpetuating a pessimistic attitude toward outcome within the field. These include the limited access people with schizophrenia have to effective interventions and the phenomenon of the “clinician's illusion,” which refers to the tendency of practitioners to assume that patients remain seriously ill when outside of the clinical care settings in which they are typically seen. Longitudinal studies, however, continue to point to a large number of people who experience improvements in their condition over time. Pressure from patients and their families, who experience periods of symptomatic relief and enhanced functioning first-hand, has led to the introduction of such concepts as “remission” and being “in” recovery with schizophrenia, in addition to the conventional notion of recovering “from” schizophrenia. These developments are consistent with recent policy initiatives by the U.S. and other governments around the world and aim to re-orient research and clinical practice from a traditional focus on effecting cure to exploring ways to encourage and assist people with schizophrenia to live meaningful lives in the face of an enduring illness.